Caracterização de amostras de dengue vírus 1, 2 e 3 e análise completa do genoma de denge vírus1 e 3 circulantes nos estados do Piauí e Minas Gerais - Leandra Barcelos Figueiredo (2009)
In terms of morbidity and mortality, Dengue virus (DENV) is currently considered one of the most important arboviruses affecting humans. The World Health Organization estimates that more than 2.5 billion people are at risk of infection with DENV and more than 100 countries in tropical regions have endemic DENV infections. DENV belongs to the genus Flavivirus of the family Flaviviridae. It is classified into four serotypes: DENV-1, DENV-2, DENV-3 and DENV-4. DENV infection causes a spectrum of symptons ranging from mild febrile illness (DF) to a severe hemorrhagic manifestations, dengue hemorrhagic fever and dengue shock syndrome (DHF / DSS). In the present work the genes C, prM / M, E, NS1, NS2a, NS2b, NS3, NS4A, NS4B and NS5 of the samples of DENV-1 and DENV-3 circulating at Minas Gerais and Piauí states were analysed and related to different clinical manifestations. These samples were used for virus isolation in C6/36 Aedes albopictus cells. RT-PCR to detect DENV RNA was performed as described by Lanciotti et al. (1992) and then was used others primers that designed to amplify full-length of Brazilian DENV-1 and DENV-3 samples. Sequencing of these samples shows several nucleotides and therefore aminoacid mutations in all analyzed genes. Phylogenetic analysis confirmed that recent Brazilian DENV-3 outbreaks are related to circulation of genotypes I and III. DENV-3 samples from Minas Gerais state showed a closer relationship with isolates from Southeast Asia and South Pacific Islands, which are samples from genotype I. However, Piaui samples were grouped with isolates identified as genotype III, which includes isolates from Sri Lanka, Central America and East Africa. Regarding DENV-1 samples, a low percentage of similarity among isolates from patients with DF and DHF was observed in all genes. The sample obtained from a patient with DHF had greater proximity to isolate Reunion, while the sample obtained from a patient with FD was grouped with isolates from Brazil, Argentina, Paraguay and other countries in America. Additionally, molecular characterization was made using the genes c-prM and E of eight samples of DENV-2 and five of DENV-3 collected in the state of Piaui. The results of analysis of these genes indicated a high similarity among these samples, as well as other sequences of DENV-2 and DENV-3 circulating in Brazil, Central and South America. Phylogenetic inferences of DENV-2 using the C-prM E genes showed that these samples are grouped together with isolates from “Asian-American” genotype.